2019
DOI: 10.3390/nu11010190
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vitamin D Supplementation on Hepcidin, Iron Status, and Inflammation in Pregnant Women in the United Kingdom

Abstract: Iron and vitamin D deficiencies are common during pregnancy. Our aim was to identify whether antenatal vitamin D3 supplementation affects iron status (via hepcidin suppression) and/or inflammation. Using a subset of the UK multicenter Maternal Vitamin D Osteoporosis Study (MAVIDOS)—a double-blinded, randomized, placebo-controlled trial (ISRCTN82927713; EudraCT2007-001716-23)—we performed a secondary laboratory analysis. Women with blood samples from early and late pregnancy (vitamin D3 (1000 IU/day from ~14 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 30 publications
3
25
1
Order By: Relevance
“…Although the differences in 25(OH)D levels between two groups were significant, we did not notice a dissimilarity in hepcidin levels between VD and CON before the run (pre). While few studies have investigated the association of vitamin D with hepcidin, our findings are consistent with the data of a study conducted by Braithwaite et al [44] where pregnant women received 1000 IU of vitamin D 3 per day for 14 weeks. Likewise, in older Mexican adults, circulating 25(OH)D concentrations were not associated with hepcidin levels [45].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the differences in 25(OH)D levels between two groups were significant, we did not notice a dissimilarity in hepcidin levels between VD and CON before the run (pre). While few studies have investigated the association of vitamin D with hepcidin, our findings are consistent with the data of a study conducted by Braithwaite et al [44] where pregnant women received 1000 IU of vitamin D 3 per day for 14 weeks. Likewise, in older Mexican adults, circulating 25(OH)D concentrations were not associated with hepcidin levels [45].…”
Section: Discussionsupporting
confidence: 92%
“…Further, in our study, serum 25(OH)D concentration was 27.82 ± 5.88 ng/mL after supplementation whereas in the trial conducted by Bacchetta et al the value was 43.5 ± 3 ng/mL [23]. Based on data presented in this study and also in the trial conducted by Braithwaite et al, we suppose that vitamin D 3 doses from 1000 IU/day to 10,000 IU/day are too small to increase 25(OH)D concentration to a sufficient level which could support inhibition of the synthesis of hepcidin at rest [44].…”
Section: Discussionsupporting
confidence: 45%
“…However, the calcitriol form of vitamin D did not reduce serum hepcidin concentrations among individuals with mild to moderate CKD [150]. Similarly, in pregnant women, vitamin D3 supplementation did not influence hepcidin, ferritin, or inflammatory status, indicating no beneficial effect in alleviating iron depletion in the subjects [151]. Further studies are needed to confirm the long-term effect of vitamin D in CKD patients.…”
Section: Novel Therapies For the Treatment Of Anemia Of Ckdmentioning
confidence: 99%
“…Bile acids facilitate the absorption and metabolism of dietary lipids and fat-soluble vitamins 22 . Vitamin D (VD), as a fat-soluble prohormone steroid, improves calcium absorption, mediates the immune response and tempers inflammation in the intestine 23 . Previous studies have found that oral probiotics can increase VD levels in plasma 24 .…”
Section: Discussionmentioning
confidence: 99%